An interpretative phenomenological analysis of the patient experience of awake craniotomy: brain tumour diagnosis to discharge - Fletcher, Kimberley J.; das Nair, Roshan; Macniven, Jamie A.; Basu, Surajit; Byrne, Paul (Wiley, 2012)
Objectives. Previous research exploring the patient experience of awake craniotomy (AC) has yielded contrasting accounts. The current study aimed to explore the lived experience of having undergone an AC in the United Kingdom.